Corrosion behaviour of aluminium alloy in palm oil methyl ester (B100) - Wan Nik, Wan Mohd Norsani; Samion, Syahrullail; Ramli, Rosliza; Rahman, Md. Mokhlesur; M.F.R., Zulkifli (Universiti Teknologi Malaysia, 2012)
The aim of this study is to determine the corrosion effect of palm oil methyl ester (POME) on aluminium alloy 5083 (AA5083). The static immersion test was carried out at 60°C for 68 days according to ASTM G-31-72. The corrosion analysis was done by using weight loss method and electrochemical test. The result from weight loss method shows the decreasing in weight loss of AA5083 which signifies the ability of POME to reduce corrosion rate. The electrochemical test shows the decreasing in polarization resistance, Rp, while the corrosion current densities, Icorr, increase. The corrosion rate reduces from 2.250mpy to 0.1946mpy. The low concentration of fatty acid C18:2 and high anti oxidant element contributes to the reduction of corrosion rate of AA5083 in POME.